In silico test of cytotoxic activity and toxicity of bioactive compounds of Aloe vera extract as a candidate drug for diabetes mellitus - Eva Ayuntya; Moh. Mirza Nuryady (Green and Tropical Laboratory for Sustainability, 2025)
Background: Diabetes mellitus is a disease characterized by hyperglycemia and metabolic disorders associated with absolute or relative deficiency in insulin action and/or secretion. Aloe vera contains several compounds with antihyperglycemic effects, and Aloe vera can mimic insulin and lower blood glucose levels. Objectives: The aim of this research is to determine the predicted physicochemical properties, toxicity and mechanisms of active compounds in Aloe vera. Methods: The method used is a computer-based experimental Molecular Docking, by predicting physicochemical, toxicity tests, bioactivity tests, protein and ligand preparation, score analysis, validation of molecular docking results, and 3D molecular visualization analysis by comparing three active Aloe vera compounds with the target protein GLP-1. Results: In silico results showed that sinapic acid, catechin, and quercitrin have good physicochemical, pharmacokinetic, and toxicity properties. In silico testing of the active Aloe vera compounds showed binding values of less than 10 with the same amino acid residues in the catechin and quercitrin compounds that bind to the active site of the GLP-1 protein. Conclusion: The active compounds contained in Aloe vera, sinapic acid, catechin, and quercitrin, can be predicted to be used as candidates for diabetes medication.